Eradication of Al-Quran Illiteracy in Garut Regency - Jahroh, Neng Siti Khotimah (Indo Consultan Energi, 2025)
Around 50% of students in Garut Regency are still unable to read the Qur'an, indicating a significant challenge in Islamic literacy and the quality of human resources. This study aims to identify strategies for eradicating illiteracy in the Qur'an (BTQ) in Garut. The method used is a literature study, which analyzes relevant literature such as books and scientific journals. The study results show the importance of developing Qur'an instructors and teacher cadres from the regional to village levels and innovation in learning methods. Collaboration with the government and non-governmental organizations is needed to form study groups and Qur'an houses and tackle assemblies in various regions. The implementation of competency certification and improving teacher welfare are also essential in order to maintain the quality and sustainability of the program. Then, this research implies that there is a need for a collaboration-based economic support system, such as business and donations, is needed to ensure teachers' welfare. This strategy can significantly reduce the Qur'an illiteracy rate in the Garut Regency.